Assessing the Impact of Local and Regional Influences on Nitrogen Loads to Buzzards Bay, MA - Williamson, Shanna C.; Rheuban, Jennie E.; Costa, Joseph E.; Glover, David M.; Doney, Scott C. (Frontiers in Marine Science, 2017)
Nitrogen and chlorophyll-a concentrations in estuarine systems often correlate positively with increased nitrogen input. To determine the interactions between nitrogen load, physical drivers, and water quality indicators, we estimated nitrogen inputs to 28 estuaries within the Buzzards Bay, Massachusetts (USA) watershed from 1985-2013. Estimates were derived by combining parcel specific wastewater disposal, point source wastewater discharge, land use, and atmospheric nitrogen deposition data with a previously verified nitrogen loading model. Linear regression analysis was used to quantify temporal trends in individual data sets and characterize relationships between variables. The land-use data indicated that fractional coverage of impervious surfaces increased with time for all sub-watersheds at the expense of vegetation and agriculture land use classes, reflecting a growth in residential unit density. Nitrogen loads decreased with time for most watersheds on the western side of Buzzards Bay, reflecting decreased atmospheric nitrogen deposition combined with management efforts to mitigate wastewater pollution. For most of Buzzards Bay’s eastern watersheds increases in nitrogen sourced from wastewater, driven primarily by the development of homes with on-site wastewater disposal, resulted in overall nitrogen load increases. The relationship between nitrogen load and mean summer in situ chlorophyll a underwent a shift to more chlorophyll a per unit nitrogen input over time that was partially correlated to climatic variables such as increased precipitation and warming water column temperatures.